Operational Status Analysis and Optimization Suggestions of Typical Dust Collectors in Coal-Fired Power Plants - Zunqiang SUN; Chenghang ZHENG; Can ZHOU; Sheng WANG; Xiuyuan MA; Yike YE (Zhongguo dianli)
In this study, 287 typical coal-fired unit dust removal facilities in 72 power plants are selected to investigate the operation status and issues of dust collectors, and corresponding suggestions are given on optimization and efficiency improvement for different types of dust collectors: For dry electrostatic precipitators (ESPs), energy saving and efficiency improvement can be achieved by adjusting electric field rapping frequency, voltage reduction rapping and power intelligent control optimization; For low-low temperature ESPs, multi-scale and multi-field coupling simulation test of the whole process can solve the problems of wear and ash deposition, and the guide components can be reasonably arranged; For bag filters, airflow distribution optimization and intelligent regulation can solve the problem of bag breakage and high energy consumption; For wet ESPs, optimization of the electrode configuration can enhance the operational stability and reduce the frequency of electric field flashover.